Front Cover Picture: Visible‐Light‐Promoted Redox‐Neutral Cyclopropanation Reactions of α‐Substituted Vinylphosphonates and Other Michael Acceptors with Chloromethyl Silicate as Methylene Transfer Reagent (Adv. Synth. Catal. 23/2018). Issue 23 (29th November 2018) - Guo, Ting; Zhang, Li; Liu, Xiaobo; Fang, Yewen; Jin, Xiaoping; Yang, Yi; Li, Yan; Chen, Bin; Ouyang, Minghui
Abstract : Thefront cover picture, provided by Yewen Fang and co‐workers, sheds new light on cyclopropanation. With chloromethyl silicate as a methylene transfer reagent, the alkene cyclopropanation has been accomplished by means of visible light‐mediated redox‐neutral catalysis. This CH2 transfer reaction features broad functional group tolerance and mild conditions. In light of the alkene scope, a great number of Michael acceptors including α, β‐unsaturated phosphonates, acrylates, ketones, amides, and sulfones are suitable substrates under these photocatalytic redox‐neutral conditions. An application of this protocol to the cyclopropanation of an estrone derivative is also presented. Details can be found in the communication on pages 4459–4463 (T. Guo, L, Zhang, X. Liu, Y. Fang, X. Jin, Y. Yang, Y. Li, B. Chen, M. Ouyang, Adv. Synth. Catal .2018, 360, 4459–4463; DOI:10.1002/adsc.201800761 ).